Pembentukkan Portofolio Optimal pada Saham JII dengan Indeks Sharpe, Treynor, dan Jensen pada Periode 2018-2023 - Khairul Alim; Anisa Rahmawati; Bayun Matsaany (Department of Mathematics, Hasanuddin University, 2023)
Investment is an activity carried out by investors by placing their funds in an asset. The purpose of investment is to gain long-term profits in the future. These profits come from changes in the price of assets in the future, which refers to the increase in the value of an asset over time. Currently, there are several types of investments. However, the type of investment that is quite widely practiced by Indonesian society is stock investment. The Indonesia Stock Exchange (IDX) groups the stocks available in the stock market into several indexes. One index that is currently receiving attention from Indonesian society is the Jakarta Islamic Index (JII). The JII is a collection of shares from companies that adhere to sharia principles in their business operations. Investment activities must be carried out carefully by conducting analysis beforehand so that investors do not make mistakes in choosing the stocks to be purchased. Several popular methods for selecting stocks are the Sharpe, Treynor, and Jensen indexes. These three indexes can be used to select the best stocks based on their respective criteria. This study combine these three indexes to prioritize the formation of a portfolio. The data used in this study is the closing value of stock prices in the JII index from March 2018 to February 2023. The optimization resulted in a composition of 69.17% for MDKA shares, 26.55% for HRUM shares, and 4.28% for BRIS shares of the total portfolio composition.